ASSESSMENT OF TEETH COLOR BEFORE AND AFTER THE BLEACHING PROCEDURE USING DIGITAL VISUALIZATION - Y.M. Ozhohan; R.Z. Ozhohan (Український стоматологічний альманах, 2024)
Dyscoloration of teeth hard tissues is a fairly common problem among the population of our country. Therefore, different methods of teeth whitening treatment are highly popular in the field of modern aesthetic dentistry. Due to a high demand of teeth whitening procedure, there is a great interest in researching the issue of color at dentistry.